2017
DOI: 10.1111/ssm.12232
|View full text |Cite
|
Sign up to set email alerts
|

Middle School Mathematics Teachers’ Perceptions of the Common Core State Standards for Mathematics and Its Impact on the Instructional Environment

Abstract: This study examines Middle School Mathematics Teachers’ (MSMTs') (N = 1,241) perceptions of the Common Core State Standards for Mathematics (CCSSM) and its impact on the instructional environment. A total of eight factors appear in the data. These factors include professional support, teachers’ use of district‐adopted and non‐district‐adopted curricular resources, influence of CCSSM assessment and teacher evaluation on the instructional environment, influence of the CCSSM on classroom instruction, teachers’ pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Building on results from an earlier survey (Davis, Choppin, Roth McDuffie, & Drake, 2013), the data analyses of Likert-type items consisted of enumerating each response category by item and calculating frequency percentages. After compiling item frequencies, we grouped items in categories to examine patterns across items (e.g., Curriculum Documents and Materials Used, Teachers’ Perceptions of CCSSM, and Teachers’ Views of State Assessments).…”
Section: Methodsmentioning
confidence: 99%
“…Building on results from an earlier survey (Davis, Choppin, Roth McDuffie, & Drake, 2013), the data analyses of Likert-type items consisted of enumerating each response category by item and calculating frequency percentages. After compiling item frequencies, we grouped items in categories to examine patterns across items (e.g., Curriculum Documents and Materials Used, Teachers’ Perceptions of CCSSM, and Teachers’ Views of State Assessments).…”
Section: Methodsmentioning
confidence: 99%
“…According to Davis et al (2018), middle mathematics teachers' knowledge and understandings of the standards for mathematical practice are limited and will require more training regarding the use of the standards. The selection of appropriate curricular resources can enhance teachers' knowledge of the standard and affect its use (Davis et al, 2017). To use the standards for mathematical practice, mathematics teachers must shift their instructional practice and not be so dependent on traditional curricular practices (Davis, 2019).…”
Section: Teacher's Role In Implementing the Standardsmentioning
confidence: 99%
“…However, their study does not provide specificity about how effective leadership activities identified in other research are enacted in hybrid patterns. The broad categories identified by Higgins and Bonne’s mask specific implementation practices such as sharing goals (Greenlee, 2008), collaborating (Moolenaar, 2012), instructional decision-making, and professional development (Davis, Choppin, McDuffie, & Drake, 2013). In addition, their study was limited to one school and reform in one subject area, leaving in question whether the patterns identified might be evidenced in widespread educational initiatives.…”
Section: Patterns Of Hybriditymentioning
confidence: 99%